Too little, too slowly: international perspectives on childhood obesity - Adrian Bauman; Harry Rutter; Louise Baur (Sax Institute, 2019)
Childhood obesity is a global concern. The prevalence of childhood overweight and obesity is increasing in many countries at all levels of development, for school-aged children and adolescents aged 5-19 years as well as preschool children younger than 5 years. Childhood obesity has implications not only for children's physical and psychological health, but it increases the risk of obesity and noncommunicable diseases into adulthood. The World Health Organization's Commission on Ending Childhood Obesity has called for governments to recognise their "moral responsibility" to act to reduce the risk; however, political action lags well behind what is needed. In this article, we examine global trends, surveillance systems and international examples of policy and progress, and describe the challenges for preventing childhood obesity.